Rehabilitation for the postsurgical orthopedic patient - Maxey, Lisa.; Magnusson, Jim.; ScienceDirect eBooks (St. Louis, Mo. : Elsevier/Mosby, 2013)
With detailed descriptions of orthopedic surgeries, this 3rd Edition provides current, evidence-based guidelines to designing effective rehabilitation strategies. Coverage of each condition includes an overview of the orthopedic patient's entire course of treatment from pre- to post-surgery. For each phase of rehabilitation, this book describes the postoperative timeline, the goals, potential complications and precautions, and appropriate therapeutic procedures. New to this edition are a full-color design and new chapters on disc replacement, cartilage replacement, hallux valgus, and transitioning the running athlete. Edited by Lisa Maxey and Jim Magnusson, and with chapters written by both surgeons and physical therapists, this text provides valuable insights into the use of physical therapy in the rehabilitation process. New coverage of current orthopedic surgeries and rehabilitation includes topics such as disc replacement, cartilage replacement, hallux valgus, and transitioning the running athlete. New full-color design and illustrations visually reinforce the content. Updated Suggested Home Maintenance boxes in every chapter provide guidance for patients returning home. References linked to MEDLINE abstracts make it easy to access evidence-based information for better clinical decision-making.
Part One: Introduction -- -- Pathogenesis of Soft Tissue and Bone Repair -- Soft Tissue Healing Considerations After Surgery -- -- Part Two: Upper Extremity -- -- Acromioplasty -- Anterior Capsular Reconstruction -- Rotator Cuff Repair -- Superior Labral Anterior Posterior Repair -- Total Shoulder Arthroplasty -- Tennis Elbow : Extensor Brevis Release and Lateral Epicondylectomy -- Reconstruction of the Ulnar Collateral Ligament with Ulnar Nerve Transposition -- Platelet Rich Plasma Injection (PRP) for the Ulnar Collateral Ligament -- Surgery and Rehabilitation for Primary Flexor Tendon Repair in the Digit -- Carpal Tunnel Syndrome -- Transitioning the Throwing Athlete Back to the Field -- -- Part Three: Spine -- -- Anterior Cervical Discectomy and Fusion -- Posterior Lumbar Arthroscopic Discectomy -- Lumbar Spine Fusion -- Lumbar Spine Disc Replacement -- -- Part Four: Lower Extremity -- -- Total Hip Arthroplasty -- Total Hip Mini Invasive -- Hip Arthroscopy -- Open Reduction and Internal Fixation of the Hip -- Anterior Cruciate Ligament Reconstruction -- Arthroscopic Lateral Retinaculum Release -- Meniscectomy and Meniscal Repair -- Autologous Chondrocyte Implantation -- Patella Open Reduction and Internal Fixation -- Total Knee Arthroplasty -- Lateral Ligament Repair of the Ankle -- Open Reduction and Internal Fixation of the Ankle -- Ankle Arthroscopy -- Achilles Tendon Repair -- Surgical Correction for Hallux Valgus Deformity -- Transitioning the Jumping Athlete -- Transitioning the Running Athlete.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Physical therapy; Orthopedic surgery -- Patients -- Rehabilitation; Postoperative care; Physical Therapy Modalities; Postoperative Care -- rehabilitation; Orthopedic Procedures -- rehabilitation; MEDICAL -- Surgery -- General; Orthopedic surgery -- Patients -- Rehabilitation; Physical therapy; Postoperative care; Revalidatie; Postoperatief beloop; Orthopedische chirurgie; Electronic books